Strengthening Environmental Law Enforcement and Dispute Resolution Through Community Education for Sustainable Environmental Tourism Governance - Sapriadi; Andi Alauddin; Ibrahim Abdullah; Fadly; Eril; Ahmad Fikri Sidiq; Asmilah Amal (www.amertainstitute.com, 2026)
Ecotourism is a sector that contributes significantly to improving community welfare and regional development. However, the expansion of tourism activities without sustainable management often leads to various issues, such as environmental degradation, conflicts over natural resource use, pollution, and disputes among the community, tourism operators, and the government. These conditions highlight the need to enhance public understanding of the legal aspects of ecotourism management and the mechanisms for effective and equitable dispute resolution. This community service initiative aims to raise public legal awareness regarding the importance of environmental law enforcement in tourism activities and to provide insight into alternative dispute resolution methods applicable when conflicts arise. The program is implemented through legal outreach, interactive discussions, and direct assistance to the community and tourism operators. The material covers principles of sustainable ecotourism management, common legal violations, law enforcement mechanisms, and dispute resolution via both litigation and non-litigation channels. The expected outcome is an increase in public knowledge and legal awareness regarding the preservation of the tourism environment and the rights and obligations of all parties, as well as the ability to resolve conflicts peacefully through deliberation, mediation, and applicable legal mechanisms. Furthermore, this initiative seeks to strengthen collaboration among the community, the government, and tourism operators to establish ecotourism governance that is sustainable and equitable, delivering economic benefits without compromising environmental protection.